The economics of foreign exchange a practical market approach - Douch, Nick (Woodhead-Faulkner, 1989)
A pioneering exploration of the relevance of economic theory to the practical realities of the foreign exchange market, this volume presents a well-reasoned, comprehensive examination of the degree to which economic theories and forecasts are helpful in predicting exchange rates. Douch, an economist who has worked closely with the foreign exchange market, argues that theoretical economic models have exhibited some serious inadequacies in forecasting the future. In an attempt to determine the real predictive value of economic theory in this context, Douch examines each of the different economic approaches in-depth and then analyzes the actual workings of the foreign exchange market from the perspective of the market participants. Particular emphasis is placed upon the reasons for the observed failure of economic theory to reliably predict exchange rate movements over time.